Pengaruh Model Pembelajaran Berbasis Game Wordwall Terhadap Kemampuan Peserta Didik Dalam Penguasaan Kosakata Bahasa Arab Kelas VIII MTsN 2 Kota Palu - Allifia Sri cahyani; Ubadah; Arda (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2023)
Some students in Madrasahs do not like Arabic because they think it is difficult and boring. In this regard, the description in this thesis departs from the problem of whether the Wordwall game-based learning model influences students' ability to master Arabic vocabulary. This type of research is a quasi-experimental involving two class VIII consisting of 68 students. Collecting data in this study used a test, namely the pretest to determine the initial ability and the posttest to determine the final ability. The results of the homogeneity test show that all data have homogeneous variants, as well as the normality test which shows that the data is normally distributed so that a hypothesis test is carried out using an independent t-test. The results of the Independent t-test showed sig 2 tailed 0.486 > 0.05, which means that H0 is accepted and H1 is rejected, which means that there is no effect of the Wordwall game-based learning model on the ability of students in mastering Arabic vocabulary for class VIII MTs Negeri 2 Palu City. The conclusions obtained are expected that educators use appropriate learning models to improve the quality of learning. For future researchers to be able to develop research using variables that are considered to have an influence on the level of mastery of students' Arabic vocabulary and choose the right learning model so that they can influence the improvement of student learning outcomes.